The Forming Age and the Evolution Process of the Brine Lithium Deposits in the Qaidam Basin Based on Geochronology and Mineral Composition - Ma, Zhe; Han, Fengqing; Chen, Tianyuan; Yi, Lei; Lu, Xiaohang; Chen, Fuhong; Liu, Xiaobao; Yuan, Wenhu (Frontiers in Earth Science, 2021)
Lithium ore deposits are divided into pegmatite and brine deposits. The Puna Plateau and the Qinghai–Tibetan Plateau (QTP) are home to the most abundant brine lithium deposits worldwide. Very few studies have investigated the chronology of brine lithium deposits. This paper reports the Optically Stimulated Luminescence (OSL) dating measurements for typical brine lithium deposits at QTP, including East Taijnar Salt Lake, West Taijnar Salt Lake, and Yiliping Salt Lake in the central Qaidam Basin. Combining the results of OSL dating with previous studies and mineral composition obtained by X-ray diffraction analysis (XRD), this study summarizes the age and characteristics of the climatic environment during the formation of brine lithium deposits in the Qaidam Basin. The main results are: 1) Brine lithium deposits in the Qaidam Basin began to form since 40 ka. Brine lithium deposits in South America formed during the middle Pleistocene and late Pleistocene, and are older than the deposits in the Qaidam Basin. The lithium deposits of Tibet formed around 4 ka, are the youngest. 2) The climate in East Taijnar Salt Lake and West Taijnar Salt Lake was extremely cold and dry during 27–4.6 ka, with a relatively humid climatic condition at ∼10 ka. After 4.6 ka, the environment was comparatively more humid around both lakes. Yiliping Salt Lake had a dry climate since 38.09 ka, and the climate in the Three Lakes area is mainly controlled by the westerlies in the Holocene; and 3) East Taijnar Salt Lake, West Taijnar Salt Lake and Yiliping Salt Lake were located in the same secondary basin during the late Pleistocene. However, tectonic activity around 40 ka led to the evolution of Yiliping Salt Lake into an independent basin. East Taijnar Salt Lake and West Taijnar Salt Lake separated around 27 ka, and then deposited the lower salt layers until the Holocene. The substantial amount of detrital minerals that the Nalinggele River brought during the Holocene led to a brief desalination of East Taijnar Salt Lake. The upper salt layer was deposited in East Taijnar Salt Lake and West Taijnar Salt Lake during this period due to the extremely dry climate.